(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This article examines the social dimensions of urban ecosystems, identified as a critical issue in contemporary urbanization. The implementation of state initiatives such as the "Green Economy" and "Green Space" programs is paramount within the context of current urbanization trends. Addressing challenges related to state and societal development requires organizing solutions based on mutual consensus with the public, incorporating public opinion in addressing existing problems, and, when necessary, delegating specific oversight responsibilities to the community. This participatory approach promotes positive changes. The necessity of utilizing innovative technologies to enhance the urban ecosystem, the focus of this research, is analyzed scientifically through direct sociological studies. The integration of human factors, human capital, and harmony with nature within the urbanization process is explored through a sociological methodology.